Digital housekeeping: Living with data. (April 2021) - Horst, Heather; Sinanan, Jolynna
The availability and affordability of memory and other services formats to store digital material has proliferated over the past 15 years. Making, sharing and storing digital material is now a mundane practice that is part of a broader ecology of living with different kinds of data. This article examines routines of managing networked technologies in the home: digital housekeeping through three core practices of sharing and storing everyday data. The first, what we will call tidying, involves the everyday routines of cleaning up the mess of data through practices such as syncing material 'in the cloud', creating inboxes and manually moving digital data such as pictures and videos to 'folders'. The second set of practices comprises more periodic, but deeper forms of sorting, spring cleaning . During digital spring cleaning, the focus is upon decluttering digital data by disposing, editing and other forms of curation whereby digital materials can be 'located' when desired in the future. The final set of practices, moving house, consists of the shift or relocation of digital data from one device or service to another. Depending upon the age and functioning of the device or service, this often involves changes in format to render digital data useful into the future, the realisation of lost data, as well as an additional assessment of the value of moving such digital material. Through fine-grained attention to the ways in which households live with digital materials, this article considers the engagement with and consequence of everyday data in our lives.